2010
DOI: 10.1001/archinternmed.2010.100
|View full text |Cite
|
Sign up to set email alerts
|

High-Dose vs Non–High-Dose Proton Pump Inhibitors After Endoscopic Treatment in Patients With Bleeding Peptic Ulcer

Abstract: Compared with non-high-dose PPIs, high-dose PPIs do not further reduce the rates of rebleeding, surgical intervention, or mortality after endoscopic treatment in patients with bleeding peptic ulcer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
0
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(47 citation statements)
references
References 45 publications
3
42
0
2
Order By: Relevance
“…Our results exhibit strong consistency with those suggested by Zhang et al who concluded that PPI is more effective than H2RA for UGH patients [58]. Another study indicates that high-dose PPI is as effective as low-dose PPI with respect to the risk of rebleeding, need for surgery and mortality [59,60]. As suggested by previous studies, the effectiveness and tolerability of PPI is not significantly affected by its administration routes.…”
Section: Discussionsupporting
confidence: 91%
“…Our results exhibit strong consistency with those suggested by Zhang et al who concluded that PPI is more effective than H2RA for UGH patients [58]. Another study indicates that high-dose PPI is as effective as low-dose PPI with respect to the risk of rebleeding, need for surgery and mortality [59,60]. As suggested by previous studies, the effectiveness and tolerability of PPI is not significantly affected by its administration routes.…”
Section: Discussionsupporting
confidence: 91%
“…In light of the data from a Cochrane analysis [41] and a meta-analysis [42,] a high-dose PPI therapy cannot generally be recommended for each case of peptic ulcer bleeding, but it seems to be justified if a high-risk bleeding stigmata is present. If the HP test was not already performed during the acute endoscopy, the report should recommended it be done ([3] chapter 4.4).…”
Section: Quality Indicators/parameters For Specific Proceduresmentioning
confidence: 99%
“…41 Examples of 'less is more' include low-dose intravenous bolus injections of proton pump inhibitors versus continuous high-dose infusions in bleeding peptic ulcers, 42 short (5 days) versus standard ( 10 days) duration oral steroids in acute exacerbations of chronic obstructive pulmonary disease, 43 short (2-4 days) versus standard (7-14 days) duration antibiotics in paediatric urinary tract infections 44 and clinically indicated versus routine (every 72 h) replacement of intravenous cannulas. 45 Where different interventions are available for the same disease, the less cost-effective options are often chosen under the influence of commercial interests or regulatory requirements.…”
Section: Select Care Options According To Comparative Cost-effectivenessmentioning
confidence: 99%